ND5 GENE MARKER REVEALS RECENT POPULATION EXPANSION OF WILD PEARSE’S MUDSKIPPER (Periophthalmus novemradiatus HAMILTON) INHABITS SETIU WETLANDS IN EAST PENINSULAR MALAYSIA - NABILSYAFIQ, M.H; GAN, H.M; ABD. MAZLAN, A.G; MAT JAAFAR, T.N.A; DANISH-DANIEL, M; SUNG, Y.Y; TAN, M.P (Malaysian Applied Biology, 2019)
Genetic variation and differences in wild Pearse’s mudskipper Periophthalmus novemradiatus populations from Setiu Wetlands in East Peninsular Malaysia were analysed using the partial mitochondrial DNA ND5 gene sequences. Among the 91 individuals sampled from six different localities, 35 novel putative haplotypes of P. novemradiatus were detected. 77% (27) of the haplotypes were unique sequences, with high level of haplotype diversity (H = 0.875) and low nucleotide diversity (π = 0.0037), contributing to the overall highly diversified gene pool of the P. novemradiatus. This reflects a large effective population size with current population expansion, which allows the retention of new alleles in populations. However, due to insufficient time, the accumulation of deeper divergent groups among haplotypes was not possible. Hap05 is the most dominant (33%) and widespread haplotype, followed by Hap11 and 31. Low genetic differentiation with high gene flow was detected between sampling sites, and no pattern for isolation by distance was observed despite being territorial creatures. All sites are at the top priority for conservation because they possess unique haplotypes that are only present at the respective location. Further samples collection from other native regions are required to provide full understanding of its genetic distribution and phylogeographical study over larger scale of geographic regions. Heuristic approach to study other species in this area prior to gazetting the Setiu Wetlands as state park is required in order to conserve the biodiversity in-situ.